Acne fulminans in the course of oral isotretinoin treatment. Presentation of cases - Magdalena Kręgiel; Anna Żuchowska; Katarzyna Tomaszewska; Agnieszka Wojciechowska; Anna Jędrowiak; Katarzyna Tabara; Wojciech Bienias; Joanna Krzysiek; Andrzej Kaszuba; Ewa Trznadel-Grodzka (Our Dermatology Online, 2017)
Isotretinoin is considered a gold standard in treating severe cases of acne. It brings lots of benefits but on the other hand can cause series of undesirable side-effects. We present 2 cases of patients suffering from acne fulminans in the course of treatment with oral isotretinoin. Acne fulminans is a very severe systemic disease and its course is difficult to foresee. The most important is rapid diagnosis and implementation of treatment. Systemic corticosteroids combined